Ultrasound Imaging of Treatment‐Needed Cardiac Rejection with CD4‐Targeted Nanobubbles. (11th July 2021) - Xie, Yu; Xie, Yuji; Chen, Yihan; Deng, Cheng; Fang, Lingyun; Li, He; Sun, Zhenxing; Gao, Tang; Liu, Jie; Yuan, Jing; Li, Yuman; Jin, Qiaofeng; et al.
Abstract: Acute cardiac allograft rejection (ACAR) is one of the main reasons for mortality after heart transplantation. The timely diagnosis of treatment‐needed ACAR is of great importance in the clinic. Molecular imaging may make accurate diagnoses at the early stage to visualize the activity of specific pathological processes. The amount of CD4 + ‐lymphocyte infiltration is a crucial index in ACAR grading. CD4‐targeted nanobubbles (NBCD4 ) are fabricated to assess the infiltrating CD4 + lymphocytes, while isotype control nanobubbles (NBIso ) are also fabricated. Animal models with ACAR grades from 0R to 3R are established. Ultrasound molecular imaging (USMI) is performed to distinguish different rejection grades with NBCD4 . In the grade 2R and 3R groups, the USMI signals of NBCD4 are significantly higher than those of NBIso . The signals of NBCD4 in the 2R group are significantly lower than those in the 3R group and significantly higher than those in the 1R and 0R groups. Moreover, the signals of NBCD4 are strongly correlated with the rejection grades and the number of infiltrating CD4 + lymphocytes. As asymptomatic rejection with 2R or higher grades should be seriously treated, USMI with NBCD4 may be a new approach to timely diagnosis of treatment‐needed ACAR. Abstract : In cardiac grafts with 2R and 3R rejection, the ultrasound molecular imaging (USMI) signals of anti‐CD4 antibody‐conjugated nanobubbles (NBCD4 ) are significantly higher than those of control nanobubbles. The USMI signals of NBCD4 can well differentiate treatment‐needed 2R and 3R rejection from 1R and 0R rejection. USMI with NBCD4 may be appropriate to detect cardiac rejection and facilitate timely treatment.